Spatial analysis and modeling of distribution pattern of wet meadows (Molinion caeruleae Koch 1926) in Goričko - Paušič, Andrej; Somodi, Imelda; Čarni, Andraž (Anali PAZU, 2022)
Contribution deals with spatial analysis and modeling as methods for detection of the landscape changes and distribution pattern of wet meadows (Molinion caeruleae Koch 1926) in Prekmurje. The aim of our study was to find explanations for the current occurrence and prediction of wet meadows in Goričko region. We analyzed potential factors that could influence the distribution of wet meadows. Plot where appear wet meadows were elaborated with digital elevation model (DEM) and provided the basic geomorphological and socioeconomic factors about wet meadows whose statistical relationships have then been established by a generalized linear model (GLM). The results show that surface of wet meadows in Goričko has been reduced in recent years and it is predicted which surfaces will be the most endangered in the future. The main factors that influence the distribution of wet meadows in Prekmurje are elevation and slope. Recent wet meadow plots occur today in hilly area, at altitude between 250 and 300 m. The most endangered wet meadows in study area are situated on flat areas in the south of the region and near to the border zones with Hungary (east, north-east) and Austria (north).
Keywords: wet meadows; digital elevation model (DEM); generalized linear model (GLM); landscape; prediction; vegetation